Integrated Regulation of AMPA Glutamate Receptor Phosphorylation in the Striatum by Dopamine and Acetylcholine - Xue, Bing (Neuropharmacology, 2016)
Dopamine (DA) and acetylcholine (ACh) signals converge onto protein kinase A (PKA) in medium spiny neurons of the striatum to control cellular and synaptic activities of these neurons, although underlying molecular mechanisms are less clear. Here we measured phosphorylation of the α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor (AMPAR) at a PKA site (S845) as an indicator of AMPAR responses in adult rat brains in vivo to explore how DA and ACh interact to modulate AMPARs. We found that subtype-selective activation of DA D1 receptors (D1Rs), D2 receptors (D2Rs), or muscarinic M4 receptors (M4Rs) induced specific patterns of GluA1 S845 responses in the striatum. These defined patterns support a local multitransmitter interaction model in which D2Rs inhibited an intrinsic inhibitory element mediated by M4Rs to enhance the D1R efficacy in modulating AMPARs. Consistent with this, selective enhancement of M4R activity by a positive allosteric modulator resumed the cholinergic inhibition of D1Rs. In addition, D1R and D2R coactivation recruited GluA1 and PKA preferentially to extrasynaptic sites. In sum, our in vivo data support an existence of a dynamic DA-ACh balance in the striatum which actively modulates GluA1 AMPAR phosphorylation and trafficking.